Xác định Epitope tế bào T trên NSP1 và GP3 của virus gây hội chứng rối loạn sinh sản và hô hấp ở lợn - Giang, Tran; Dien, Phan; Hiếu, Đồng; Chung, Wen (Tạp chí Khoa học Nông nghiệp Việt Nam, 2024)
Porcine reproductive and respiratory syndrome virus (PRRSV) has become one of the primary diseases affecting pig breeding worldwide. Although vaccines are available, the disease is still widespread and the virus is frequently reintroduced to pig farms. The development of an effective vaccine to control PRRSV outbreak is an imperative requirement because of a devastating economic impact on the swine industry. Therefore, it has become essential to understand what constitutes the basis for protective immunity in PRRSV infection when designing new PRRSV vaccines. We used bioinformatics to identify T-cell epitopes for PRRS virus vaccine development. PRRSV strain ATCC VR-2332 (U87392.3) was used as the reference virus in this study. To achieve this goal, 12 peptides spanning the sequence of PRRSV (U 87392.3) were screened using the IFN-γ ELISpot assay. These peptides were identified for their ability to elicit a recall INF-γ response from peripheral blood mononuclear cells (PBMCs) isolated from 3 pigs infected with PRRSV HF6-2. The results led to the identification of two peptides located in ORF1b and ORF3 that appear to contain T-cell epitopes. These findings might provide valuable information to develop new and more efficacious vaccines against PRRSV.